Implikasi Komitmen Organisasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. 786 Jakarta - Wahyuni, Putri Diana; Zaharuddin, Zaharuddin; Hanaffy, Jamal (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
In the context of increasingly intense business competition, employee performance becomes a crucial factor for a company's success. PT. 786 Jakarta, as a rapidly growing company, faces the challenge of enhancing employee productivity. Organizational commitment and work discipline are considered essential elements that influence employee performance. Therefore, this study aims to analyze the impact of organizational commitment and work discipline on employee performance at the company. This research is quantitative in nature, descriptive, and associative. The population for this study consists of employees at PT. 786 Jakarta. The sampling technique employed is random sampling, with a sample size of 33 employees from PT. 786 Jakarta selected as respondents. Based on the research findings, it can be concluded that both organizational commitment and work discipline have a positive and significant impact on employee performance at PT. 786 Jakarta. Organizational commitment is shown to have a greater contribution to performance improvement compared to work discipline, although both play complementary roles in enhancing productivity. These findings emphasize the importance for the company to strengthen organizational commitment and maintain work discipline as key strategies in improving overall employee performance.